STRATEGI KOMUNIKASI MARKETING PUBLIC RELATIONS DALAM MEMBERIKAN PELAYANAN BAGI KONSUMEN (STUDI PADA CUSTOMER SERVICE PT RATU HOTEL BIDAKARA SERANG BANTEN - Tri Hapsari, H.N. Lintang; Yuniarti, Tatik (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2015)
Ratu Hotel Bidakara is the newest 4 star hotel with  MICE (Meeting, Incentive, Convension,&  Exhibition)  category  in  Serang  city,  Banten  Province.  As  a  strategy  to  survive  in competition similar business in Serang City, Ratu Hotel Bidakara takes one step through the sinergy role of Public Relations and Marketing Public Relations in customer service.This study examines more about the role and effort of Marketing Public Relations as a customer service of Ratu Hotel Bidakara to improve service to the customers. The purpose of this study is to analyze the communication strategy and service system, as well as the efforts of Ratu Hotel  Bidakara  in  empowering  all  their  customer  service  officers.  Then  analyzed  the difference made to the general service and VIP guests and analyze coorporate images. This study used descriptive qualitative method, researcher explores the role and communication strategic is done by Marketing Public Relations as a customer service. Information obtained through  observation  and  depth  interviews  with  informants.  The  result  concluded  that Marketing Public Relations activities in Ratu Hotel Bidakara who perform three functions in accordance with the Ltyle theory (1996) used. First, the pre-transaction activities act as a Communication Technician, served as Deskman (providing information about products and services of the hotel). Second, in-transaction activity act as a receptionist and also as an Expert Prescriber (expert advisor), who performed the role of Customer Relations Officer (to maintain good relations with customers). Third, post-transaction activities act as a Communication Facilitator, Marketing Public Relations served as a communicator (a channel of communication between consumers and firms in response to consumer complaints)